1979
DOI: 10.1152/jappl.1979.46.3.451
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and speed of movement in relation to age and muscle morphology

Abstract: Maximum values for isometric strength, dynamic strength, and speed of movement (MEV) in the quadriceps muscle were measured in 114 male subjects who were between 11 and 70 yr. Biopsy samples were taken from the quadriceps muscle in 51 of the subjects (22-65 yr. old). Isometric and dynamic strength increased up to the third decade, remained almost constant to the fifth decade, and then decreased with increasing age. However, no measurable external atrophy of the quadriceps muscle, explaining the decline in stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

47
510
6
19

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 946 publications
(582 citation statements)
references
References 0 publications
47
510
6
19
Order By: Relevance
“…Interestingly, when isometric muscle force is expressed as a percentage of body weight, the losses with advancing age appear to be minimal ( Table 2). The loss of force with aging has been attributed to both a loss of functioning motor neurons as well as a reduced number of fast-twitch muscle fibers (29). Both animal and human studies have demonstrated that loading rate, rather than load magnitude, is the critical factor for cartilage damage in OA (30).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when isometric muscle force is expressed as a percentage of body weight, the losses with advancing age appear to be minimal ( Table 2). The loss of force with aging has been attributed to both a loss of functioning motor neurons as well as a reduced number of fast-twitch muscle fibers (29). Both animal and human studies have demonstrated that loading rate, rather than load magnitude, is the critical factor for cartilage damage in OA (30).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is characterized by a loss of skeletal muscle mass and an associated deterioration in the functional properties of the remaining muscle tissue (Goodpaster et al 2006;Larsson et al 1979). The demographic changes projected for the developed countries and the impact that these changes in muscle function will have on health care costs and quality of life, have made understanding the mechanisms underlying these agerelated changes in skeletal muscle contractility of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…The latter includes fiber loss and atrophy (Larsson et al 1979;Sato et al 1984;Lexell et al 1988), impairments in the excitation-contraction process (Delbono et al 1995;Wang et al 2002), and perturbations to actomyosin cross-bridge function (Larsson et al 1997; Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001). These factors are specific to the mode of muscle contraction, impacting force during isometric and shortening contractions but having much less effect on force during lengthening or eccentric, muscular activity (Porter et al 1997;Poulin et al 1992;Phillips et al 1991;Ochala et al 2006;Hortobagyi et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults exhibit reduction in fast twitch muscle fibers in comparison to slow twitch muscle fibers [26,27]. The age-related changes in the skeletal muscle property, such as muscle fiber types may hinder quick gait adjustments required for successful ambulation over slippery floor surfaces.…”
Section: Introductionmentioning
confidence: 99%